Learning and Teaching Academic Standards for Environment and Sustainability. - McBain, Bonnie; Phelan, Liam; Brown, Paul; Brown, Valerie; Hay, Iain; Horsfield, Richard; Taplin, Ros; Ferguson, Anna (Office for Learning and Teaching, 2016)
Standards statement from a project commissioned by the Australian Council of Environmental Deans and Directors which aimed to establish national teaching and learning standards for higher education qualifications in Environment and Sustainability. The standards are grouped into four domains: transdisciplinary knowledge, systemic understanding, skills for environment and sustainability, and ethical practice. Environment and sustainability concerns are shared across a wide range of disciplines spanning the humanities and the social and natural sciences. This project employed a comprehensive and sophisticated consultative process through 2014 to ensure broad support for the standards and to strengthen a common sense of community amongst Environment and Sustainability scholars from these diverse disciplinary backgrounds.